2016
DOI: 10.1093/scan/nsw060
|View full text |Cite
|
Sign up to set email alerts
|

Perceived live interaction modulates the developing social brain

Abstract: Although children's social development is embedded in social interaction, most developmental neuroscience studies have examined responses to non-interactive social stimuli (e.g. photographs of faces). The neural mechanisms of real-world social behavior are of special interest during middle childhood (roughly ages 7-13), a time of increased social complexity and competence coinciding with structural and functional social brain development. Evidence from adult neuroscience studies suggests that social interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 60 publications
(84 reference statements)
1
21
0
1
Order By: Relevance
“…Nevertheless, our analysis of mentalizing ROIs showed a consistent pattern, with differences in activation to Peer versus Character conditions decreasing with age in all ROIs. Though correlations between age and activation to Peer and Character conditions, respectively, did not reach significance, the decreasing difference may have been driven by increasing mentalizing in response to Character but not Peer conditions, which would accord with previous findings of increasing activation of dMPFC to non-interactive social stimuli across middle childhood (Rice et al, 2016) and in adolescence relative to adulthood (reviewed in Blakemore, 2008). It is also possible that our task is more similar to the real-life peer interactions of younger than older children.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Nevertheless, our analysis of mentalizing ROIs showed a consistent pattern, with differences in activation to Peer versus Character conditions decreasing with age in all ROIs. Though correlations between age and activation to Peer and Character conditions, respectively, did not reach significance, the decreasing difference may have been driven by increasing mentalizing in response to Character but not Peer conditions, which would accord with previous findings of increasing activation of dMPFC to non-interactive social stimuli across middle childhood (Rice et al, 2016) and in adolescence relative to adulthood (reviewed in Blakemore, 2008). It is also possible that our task is more similar to the real-life peer interactions of younger than older children.…”
Section: Discussionsupporting
confidence: 84%
“…Still, as in the adult literature, neuroimaging studies on the effect of social interaction on social cognition in middle childhood are scarce. In one such study, similar to the aforementioned study in adults (Rice & Redcay, 2016), perceived live versus recorded speech engaged the TPJ and precuneus in children aged 7–13 (Rice et al, 2016). In a separate experiment in a similar age group, receiving feedback from a peer after sharing information about oneself activated social-cognitive and reward regions, and the magnitude of the social-interactive effect in social-cognitive regions increased with age (Warnell et al, 2018).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Indeed, previous studies with children have indicated that similar regions are active simply when listening to speech from a perceived social partner, even without any explicit demands (Rice, Moraczewski, & Redcay, 2016). Interestingly, TPJ and STS did not show the same interaction between contingency and social context present in reward circuitry; these regions were still engaged even when the child viewed messages indicating that the peer was unavailable.…”
Section: Social Cognitive Systems Support Ongoing Interactionmentioning
confidence: 77%
“…One possible explanation is that the social cognitive network is involved when processing any socially relevant information, perhaps due to cognitive elaboration about what the social partner thought of the child's answer or due to anticipated future interaction. Indeed, previous studies with children have indicated that similar regions are active simply when listening to speech from a perceived social partner, even without any explicit demands (Rice, Moraczewski, & Redcay, 2016).…”
Section: Social Cognitive Systems Support Ongoing Interactionmentioning
confidence: 99%